PENGARUH STANDAR OPERASIONAL PROSEDUR DAN PENGAWASAN TERHADAP KINERJA PRAMUNIAGA PASARAYA SRIRATU PEMUDA SEMARANG - Nugraheni, Ratih; Prihatini, Apriatni Endang; Budiatmo, Agung (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Performance is the result of work that attained by people to implement their duties based on accomplishment, experience, sincerity and time. External factors that affect salesperson's performance are standard operating procedures (SOP) and monitoring. This research aimed to find out the impression of SOP and monitoring to salesperson's performance. The type of this research is explanatory research, by censussing 63 respondents. The analysis method using multiple regression analysis,korelasi,cross tabel and determinasi koefisien. Measurement scale using Likert Scale. It analyzed by linear test and significance teat that supported by SPSS 16.0.The results showed a positive and significant influence between standard operating procedures (SOP) and monitoring toward the satisfaction of salesperson's performance partially, the influence of standard operating procedures (SOP) and monitoring for a combination toward salesperson's performance.